1992
DOI: 10.1007/bf00931705
|View full text |Cite
|
Sign up to set email alerts
|

A survey ofBlastocystis in reptiles

Abstract: A total of 28 species of reptiles were investigated for Blastocystis using light microscopy and in vitro culture in biphasic egg slant medium. Blastocystis species were detected in 8 (28.6%) of these 28 species in 3 tortoises (Geochelone elephantopus, G. elegans and G. carbonaria), 3 snakes (Boiga dendrophilla, Python reticulatus and Elaphe radiata), 1 crocodile (Crocodylus porosus) and 1 iguana lizard (Cyclura cornuta). The reptilian Blastocystis appeared to be morphologically similar to B. hominis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Moreover, people working closely with animals in zoos and abattoirs and food handlers (14,31,32) are at higher risk of acquiring Blastocystis infection. In addition, transmission of Blastocystis organisms could also be frequent between animals, especially in confined areas, such as zoological gardens and circuses, where fecal contamination of grass and fodder is common (37,42). Thus, in light of our data and those from the literature, it is reasonable to speculate that contamination by Blastocystis organisms can occur via animalto-animal, human-to-animal, and animal-to-human routes.…”
Section: Resultsmentioning
confidence: 53%
“…Moreover, people working closely with animals in zoos and abattoirs and food handlers (14,31,32) are at higher risk of acquiring Blastocystis infection. In addition, transmission of Blastocystis organisms could also be frequent between animals, especially in confined areas, such as zoological gardens and circuses, where fecal contamination of grass and fodder is common (37,42). Thus, in light of our data and those from the literature, it is reasonable to speculate that contamination by Blastocystis organisms can occur via animalto-animal, human-to-animal, and animal-to-human routes.…”
Section: Resultsmentioning
confidence: 53%
“…Axenic cultures of Blastocystis isolates are important for molecular and biochemical studies. Axenization can be achieved by the addition of antibiotic cocktails to eliminate contaminating bacteria and yeasts, and a variety of antibiotic mixtures have been described, with various levels of success (45,128,164,269,319). The process is generally laborious and may take weeks to months, and the successful elimination of microbial contaminants is not guaranteed.…”
Section: Laboratory Culturementioning
confidence: 99%
“…In addition to antibiotic treatment, some authors noted improved success when physical methods were employed during axenization to separate parasites from the bulk of the bacterial load. This includes differential centrifugation (269), density gradient separation (128), and colony growth (45,164). Such methods enrich for the parasite and provide a growth advantage.…”
Section: Laboratory Culturementioning
confidence: 99%
“…had also been isolated from various animal sources including cockroaches (Zaman et al 1993), pigs, cattle (Quilez et al 1995a, and reptiles (Teow et al 1992). Molecular analysis of isolates from animal sources had shown that there exist many Blastocystis isolates that were closely related to isolates from animal hosts, suggesting that animals are a potential source of human infection (Abe et al 2003a, b, c;Noël et al 2005;Thathaisong et al 2003;Yoshikawa et al 1996).…”
Section: Introductionmentioning
confidence: 95%